Sosialisasi dan Workshop Digital Marketing sebagai Upaya Pengembangan Usaha Masyarakat Desa Kalibenda, Kecamatan Ajibarang, Kabupaten Banyumas - Yesy Diah Rosita; Dany Candra Febrianto; Andi Prademon Yunus; Aulia Desy Nur Utomo (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
Digital marketing has been a foundation for the business development strategy in the digital era. Even though, the utilization of digital marketing is not evenly applied, especially on the rural area such as in Desa Kalibenda, Kabupaten Banyumas. This community service aims to improve understanding and skills on digital marketing to the resident of the Desa Kalibenda for the potential utilization of digital marketing. Through workshop and seminar, participants are introduced to basic concept of the digital marketing such as media social strategies, browser optimization, and data analytics. The workshop shows significant understanding improvement as well as the positive impact on participant skills on utilizing the digital technology for UMKM marketing measured by post-test after the workshop. As a result, the workshop is suggested to continue and extend the similar program for other region to improve the local UMKM competitiveness in the connected digital market.